Antropoceno, agroecologia e o movimento de produção de alimentos orgânicos da serra gaúcha: conceitos, histórico e interlocuções - Suliani, Carla Rodrigues Dal Prá (2022)
This work explores a universe translated by environmental history to build a new look at the future. It is a text built from many readings that support opinions to test propositional theories of solutions, as well as criticisms applicable to the studied context. For Environmental History, among its objectives, goes back to the investigation of the causes of ecological problems that are reflected today. Whether it's pollution, ocean acidification, forest devastation, species extinction. In short, the Anthropocene is the proposition of an era where humans are the main geological force on changes in the planet. Since agriculture is an anthropic activity with a great impact on the world's biodiversity, it demands and justifies observation in the midst of this process. In this way, the work in question performs an analysis of the organization of the movement of organic food production in the core of the Serra of agroecology, history and perspectives in the face of the Anthropocene. The problem that guides this study: Are there contributions in the constitution of the organization of the local organic production movement to face the contemporary challenges imposed by the Anthropocene? The objectives of the work are: To analyze the organization of the organic food production movement in Serra Gaúcha, history and perspectives in the Anthropocene. To achieve this purpose, specific goals were defined: 1. Review and present concepts and processes of Anthropocene evolution. 2. Describe the historical trajectory about the evolution of the movement that resulted in the current local organic productive context describing what challenges are currently perceived 3. Understand how agroecology and the Anthropocene are happening at a time of uncertainty due to the pandemic. The research methodology was qualitative and uses as tools: bibliographic and documentary research, printed and online publications, scientific articles, books, published research and interviews, videos and historical series of data and documents and personal files made available. As a result of chapter 1, it is concluded that: The Anthropocene, even if not officially recognized as a Geological Era, is already accepted by the academy due to the visible changes easily verified since the Great Acceleration. While this acceptance will soon take us to another phase of consciousness where, endowed with intellectual capacity as humanity, we recognize the mistakes that brought us here and build solutions to mitigate their paths. So, are we on the way to experiencing a self-aware Anthropocene? Chapter 2 analyzed agroecological development and its local and global challenges. It can be concluded that it is a movement of collective awareness initiated from the questioning of the current mode of production and since its beginning it has accumulated followers and achievements for the collective and the environment. Chapter 3 highlights biophysical data about the current perceived situation of the Anthropocene, perceived local impacts and aspects of everyday local agroecology at the time of the pandemic. With this block, it is concluded that anthropocentric changes are locally perceptible and important studies point to agroecology as a carrier of solutions. It can be seen that the pandemic requires adaptation of ecological farmers, in addition to their union for disputes in defense of maintaining aspects already conquered in the past. At the end, the study lists some perceptions about the central problem. And it allows to conclude mainly that the agroecological model happens with practices contrary to those that boosted the advent of the Anthropocene, so it has the capacity to contribute to the construction of more adequate production systems.